2014
DOI: 10.1051/0004-6361/201322971
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectral modelling of the AGN obscuring region in the CDFS: Bayesian model selection and catalogue

Abstract: Aims. Active galactic nuclei are known to have complex X-ray spectra that depend on both the properties of the accreting super-massive black hole (e.g. mass, accretion rate) and the distribution of obscuring material in its vicinity (i.e. the "torus"). Often however, simple and even unphysical models are adopted to represent the X-ray spectra of AGN, which do not capture the complexity and diversity of the observations. In the case of blank field surveys in particular, this should have an impact on e.g. the de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
1,263
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,391 publications
(1,339 citation statements)
references
References 86 publications
14
1,263
3
5
Order By: Relevance
“…Ross & Fabian 2005;Brightman & Nandra 2011a). However, Buchner et al (2014) found that more simplistic models such as ours are generally sufficient to reproduce the observed spectral shape of individual, distant AGNs, especially considering our analysis uses broad-band fluxes rather than performing a detailed X-ray spectral analysis. To describe our X-ray spectral model requires three additional parameters-the photon index, Γ, the scattered fraction, fscatt, and the relative normalization of the reflection component, R-which we introduce as "nuisance" parameters (collectively designated by ξ) in our Bayesian analysis.…”
Section: Probability Distribution Function For a Single Sourcementioning
confidence: 86%
See 2 more Smart Citations
“…Ross & Fabian 2005;Brightman & Nandra 2011a). However, Buchner et al (2014) found that more simplistic models such as ours are generally sufficient to reproduce the observed spectral shape of individual, distant AGNs, especially considering our analysis uses broad-band fluxes rather than performing a detailed X-ray spectral analysis. To describe our X-ray spectral model requires three additional parameters-the photon index, Γ, the scattered fraction, fscatt, and the relative normalization of the reflection component, R-which we introduce as "nuisance" parameters (collectively designated by ξ) in our Bayesian analysis.…”
Section: Probability Distribution Function For a Single Sourcementioning
confidence: 86%
“…Whether the observational evidence supports such changes in the shape of the XLF has been a matter of debate (e.g. A10, Aird et al 2008;Fiore et al 2012;Ueda et al 2014;Buchner et al 2015). Furthermore, a physical interpretation of this complex parametrization is difficult.…”
Section: Luminosity and Density Evolution (Lade)mentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra and the best-fit models for these sources are reported in Figure 4. This disagreement is not unusual, several works using low-energy data have thus far attempted the spectral identification of distant CT sources in the medium/deep survey fields (e.g., Tozzi et al 2006;Georgantopoulos et al 2007Georgantopoulos et al , 2009Georgantopoulos et al , 2013Comastri et al 2011;Feruglio et al 2011;Brightman & Ueda 2012;Brightman et al 2014;Buchner et al 2014;Lanzuisi et al 2015), and given the range of possible spectral shapes for CT sources and the limited counting statistics (from few tens to ∼100 counts) for these faint sources, especially at the highest energies 5 6 keV  -where the effective area starts to drop, researchers have always struggled to consistently identify CT sources (see, e.g., Castelló-Mor et al 2013). Moreover, their analysis, at least for sources with redshifts 2  (i.e., the great majority of the potential contributors to the CXB, according to populationsynthesis models), have been limited by sampling of the restricted lower-energy part of the reflection component and of the heavily obscured primary emission.…”
Section: Sifting Through Candidate Ct Sourcesmentioning
confidence: 99%
“…As a robustness test we used a Bayesian fitting code (BXA; Buchner et al 2014) with flat priors for the same parameter ranges as our standard fitting method and obtained consistent results. A non-negative prior for the additional Gaussian flux did not improve the constraints.…”
Section: Fitting Individual Spectramentioning
confidence: 91%